Persistence of monopoly and research specialization - Philipp Weinschenk (Max Planck Institute for Research on Collective Goods, 2009)
We examine the persistence of monopolies in markets with innovations when the outcome of research is uncertain. We show that for low success probabilities of research, the incumbent can seldom preempt the potential entrant. Then the efficiency effect outweighs the replacement effect. It is vice versa for high probabilities. Moreover, the incumbent specializes in safe research and the potential entrant in risky research. We also show that the probability of entry has an inverted U-shape in the success probability. Since even at the peak entry is rather unlikely, the persistence of the monopoly is high.
Keywords: L12; O31; 330; Persistence of Monopoly; Efficiency Effect; Replacement Effect; Stochastic Innovations; Innovation; Monopol; Industrielle Forschung; Stochastischer Prozess; Arbeitsteilung; Markteintritt; Innovationswettbewerb; Potenzieller Wettbewerb; Theorie